Circular - Blewitt, Trevor
042-0023-001 SPANISH MEDICAL AID COMMITTEE President: Rt. Hon. LORD ADDISON Vice-Presidents: Dr. CHARLES BROOK. L C.C. Dr. DAVID FORSYTH VICTOR GOLLANCZ Professor JULIAN HUXLEY Rt. Hon. Sir WILLIAM JOWITT. K.C. Sir WALTER T. LAYTON The EARL OF LISTOWEL Miss MEGAN LLOYD GEORGE, MP. TOM MANN D.N. PRITT. K.C. M.P. Miss ELEANOR RATHBONE. M.P. Miss ESTHER RICKARDS. L.C.C. JOS. ROBINSON, M.D. Dr. MAUDE ROYDEN Sir ARCHIBALD SINCLAIR. MP. BEN TILLETT Dr JANET VAUGHAN ALFRED M. WALL Miss REBECCA WEST Chairman : Dr. H.B. MORGAN. M.D. Vice-Chairman: Dr. SOMERVILLE HASTINGS, L.C.C. Treasurers: Viscountess HASTINGS Professor J.R. MARRACK Hon. Secretary: Mrs. LEAH MANNING, J.P. Organising Secretary: GEORGE JEGER, J.P. 24 NEW OXFORD STREET W.C.1 Telephone: HOLburn 1866 0605 PLEASE NOTE NEW ADDRESS 69, GT. RUSSELL ST., W.C.1. (Same Telephone Numbers.) 14th July 1939. Dear Friends, We are not issuing a printed Bulletin at the moment for reasons of economy, but we wish to keep you informed of the numerous tasks which have devolved upon the Committee in connection with the Refugee Camps in France, refugees in this country, and the Refugee Ships which have transported the victims of the Spanish struggle to a new land of freedom, Mexico, whence they can carry on the struggle for the ultimate victory of the Spanish peoples in the New and Old World. The work of the Committee may not be as spectacular as in the past, but it is if anything more important. The Committee believes, in common with its Spanish brothers in the struggle against Fascism, that now more than ever is a moment for faith and confidence. So, with a reduced staff, the Committee carries on. We ask all our supporters to continue their generous aid for the Spanish people. Yours fraternally, Trevor Blewitt, (Bulletin Editor). P.S. The Holborn Spanish Aid Committee is appealing for jumble for their next sale in August. Goods of any description will be gratefully received at the above address. 292/946/42/23